![4x - 12 = 2 .(x + 7) + 6 4x - 12 = 2 .(x + 7) + 6](https://tex.z-dn.net/?f=4x+-+12+%3D+2+.%28x+%2B+7%29+%2B+6)
4x-12=2.(x+7)+6
Soluções para a tarefa
Respondido por
7
4x-12=2.(x+7)+6
4x - 12 = 2x + 14 + 6
4x - 2x = 14 + 6 + 12
2x = 20 + 12
2x = 32
x = 32/2
x = 16
4x - 12 = 2x + 14 + 6
4x - 2x = 14 + 6 + 12
2x = 20 + 12
2x = 32
x = 32/2
x = 16
Perguntas interessantes
Química,
10 meses atrás
Geografia,
10 meses atrás
Ed. Física,
10 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Física,
1 ano atrás
Física,
1 ano atrás